Applying technical and fundamental analysis to identify undervalued financial and conglomerate stocks in SGX - Lim, Marcus Zheng Hui (Nanyang Technological University, 2023)
Many analysts and investors use many different methods to analyse a company and tries to beat the market. In this paper, fundamental, technical and news analysis will be applied to stocks in the financial and conglomerate sectors. Fundamental analysis will be split into 2 section namely quantitative and qualitative analysis which is used to rank the companies in the 2 sectors. Following, technical analysis is used by applying simple moving average cross over on historical price data over a period of 5 years from 2017 to 2021. Finally, news analysis is used to determine the impact of global news have on the individual stocks. The study emphasizes the value of using fundamental analysis to pick fundamentally strong businesses, technical analysis for entry and exit trades, and news analysis to comprehend how news can significantly affect stock prices to allow investors to profit from investing.